Hubungan Kecepatan Angin dan Kelembaban Udara terhadap Pemencaran Konidium Cercospora nicotianae pada Tembakau - RAFIQI TANTAWI, AHMAD (AGRITROP; Vol. 26, No. 4 Desember 2007)
One of the limiting factors in tobacco production is frogeye leaf spot, a fungal disease caused by C. nicotianae. Epidemic of this disease was supposed to have a close relationship with weather aspects, such as wind velocity, temperature, solar radiation intensity and relative humidity. An experiment was conducted to determine relationship between wind velocity and relative humidity to conidial dispersal on tobacco. The experiment carried out at Mycology Laboratory, Study Program of Plant Pest and Disease, Faculty of Agriculture, UGM and two tobacco plantations in Jember and Klaten. The results showed that conidia was dispersed by wind and can be trapped by Kiyosawa type of wind vane rotary spore trap. Conidia were dispersed in dry, and moist, as well as wet months. During the dry and moist month, conidia was trapped since 06.00 a.m. the trapping reached its peak at 02.00-06.00 p.m., while in wet month at 10.00 a.m. to 14.00 p.m. Dry air condition was needed in conidium releasing. The number of conidia was decreased when relative humidity increased.
Keywords: Cercospora nicotianae, tobacco, wind velocity, relative humidity, conidial dispersal